Characterizing the impact of MnO2 addition on the efficiency of Fe0/H2O systems - Viet Cao (Nature Portfolio, 2021)
Abstract The role of manganese dioxide (MnO2) in the process of water treatment using metallic iron (Fe0/H2O) was investigated in quiescent batch experiments for t ≤ 60 d. MnO2 was used as an agent to control the availability of solid iron corrosion products (FeCPs) while methylene blue (MB) was an indicator of reactivity. The investigated systems were: (1) Fe0, (2) MnO2, (3) sand, (4) Fe0/sand, (5) Fe0/MnO2, and (6) Fe0/sand/MnO2. The experiments were performed in test tubes each containing 22.0 mL of MB (10 mg L−1) and the solid aggregates. The initial pH value was 8.2. Each system was characterized for the final concentration of H+, Fe, and MB. Results show no detectable level of dissolved iron after 47 days. Final pH values varied from 7.4 to 9.8. The MB discoloration efficiency varies from 40 to 80% as the MnO2 loading increases from 2.3 to 45 g L−1. MB discoloration is only quantitative when the operational fixation capacity of MnO2 for Fe2+ was exhausted. This corresponds to the event where adsorption and co-precipitation with FeCPs is intensive. Adsorption and co-precipitation are thus the fundamental mechanisms of decontamination in Fe0/H2O systems. Hybrid Fe0/MnO2 systems are potential candidates for the design of more sustainable Fe0 filters.